In vitro assessment of multistrain probiotic on its safety, biofilm formation capability, and antimicrobial properties against Aeromonas hydrophila - Wye, Olivia Sze Lee; Puvanasundram, Puvaneswari; Lim, Keng Chin; Karim, Murni (Universiti Putra Malaysia, 2022)
Probiotics have been increasingly considered an alternative to antibiotics in combating disease outbreaks. Combined probiotics have been studied to possibly harbor synergistic effects that could provide better protection for aquatic species. Three potential probiotics, which had shown in vitro antagonism towards Aeromonas hydrophila in this study, were Bacillus amyloliquefaciens (L9, isolated from the blue swimming crab), Lysinibacillus fusiformis (A2, isolated from a microalga), and Enterococcus hirae (LAB3, isolated from the Asian seabass) were combined into a probiotic mixture. The probiotic mixture produced significantly higher biofilm (P < 0.05) (2.441 ± 0.346) than A. hydrophila (0.578 ± 0.124) during 24-h and showed a continuous increase in production at 48-h and 72-h time intervals, respectively. Furthermore, no hemolytic action was observed when the probiotic mixture was streaked on sheep blood agar (5%), whereas A. hydrophila presented α-hemolysis. The lowest concentration of the probiotic mixture (107 CFU mL-1) significantly inhibited (P < 0.05) the growth of A. hydrophila at 106 CFU mL-1 after 24 h of incubation, where bacterial count in the treatment was 6.595 ± 0.218 CFU mL-1, which was significantly lower (P < 0.05) than the control (7.247 ± 0.061 CFU) mL-1. Significant reduction (P < 0.05) in Aeromonas count from 7.532 ± 0.026 CFU mL-1 to 6.883 ± 0.015 CFU mL-1 was observed at 12 hours of co-incubation. Hence, this research suggests that the probiotic mixture of L9, A2, and LAB3 potentially confers protection against A. hydrophila infection due to their characteristics meeting the criteria of probiotics.